2014
DOI: 10.1007/s10661-014-3960-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of soil contamination hotspots with veterinary antibiotics using heavy metal concentrations and leaching data—a field study in China

Abstract: In regions with high livestock densities, the usage of antibiotics and metals for veterinary purposes or as growth promoters poses a risk in manured soils. We investigated to which degree the concentrations and depth distributions of Cu, Zn, Cr and As could be used as a tracer to discover contaminations with sulfonamides, tetracyclines and fluoroquinolones. Besides, we estimated the potential vertical translocation of antibiotics and compared the results to measured data. In the peri-urban region of Beijing, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 45 publications
4
10
2
2
Order By: Relevance
“…Among five detected SAs, SMX revealed the highest average concentration of 0.57 μg kg −1 dw and detection frequency of 44 %. This result was consistent with several previous reports with the low concentration of SAs in the surface soil (Karcı and Balcıoğlu 2009;Tamtam et al 2011), whereas Ostermann et al (2014) have found significantly higher SAs concentration (110 μg kg −1 ) in the topsoil of agricultural fields in the peri-urban region of Beijing, China. As for MLs, much lower concentration and detection frequency than SAs in the urban soil was observed, and ROX was detected with maximum detection frequency of 26 % and average concentration of 0.06 μg kg −1 dw.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Among five detected SAs, SMX revealed the highest average concentration of 0.57 μg kg −1 dw and detection frequency of 44 %. This result was consistent with several previous reports with the low concentration of SAs in the surface soil (Karcı and Balcıoğlu 2009;Tamtam et al 2011), whereas Ostermann et al (2014) have found significantly higher SAs concentration (110 μg kg −1 ) in the topsoil of agricultural fields in the peri-urban region of Beijing, China. As for MLs, much lower concentration and detection frequency than SAs in the urban soil was observed, and ROX was detected with maximum detection frequency of 26 % and average concentration of 0.06 μg kg −1 dw.…”
Section: Resultssupporting
confidence: 93%
“…The concentrations of SMX and ROX in our study were higher than those in the agriculture soil after long-term wastewater irrigation in Paris (Tamtam et al 2011) and in the agriculture soil fertilized with poultry or cattle manure (Karcı and Balcıoğlu 2009), but lower than the SMX concentration of 4 μg kg −1 determined in peri-urban agricultural soil after approximately 20 years irrigation with untreated wastewater in Mexico City (Dalkmann et al 2012). In contrast, (Ostermann et al 2014) have found a maximum SMZ concentration of 110 μg kg −1 in peri-urban agricultural soil from Beijing, while SMZ was only detected with the maximum concentration of 2.8 μg kg −1 in urban soil from Beijing and Shanghai in our study.…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…There is already clear evidence of overuse of nutrients in some parts of China (SAIN, 2010) and this is causing undesirable impacts on the environment (Norse, 2015;Guo et al, 2010;Le et al, 2010;, with key problems associated with the discharge of effluent (including the liquid fraction of solid manure, whole slurry and the liquid fraction from separated slurry) from livestock farms and over-application to many crop types in China Lu et al, 2012;Sims et al, 2013;Xue et al, 2013b;Yan et al, 2013;Ostermann et al, 2014;Powlson et al, 2014). A more rational approach to the use of nutrients in Chinese agriculture, especially an improvement in manure nutrient efficiency should result in reduced inorganic N fertiliser use, which would deliver a range of benefits, including a reduced impact on the environment and improved farmer incomes, without crop yield penalties.…”
Section: Introductionmentioning
confidence: 99%